Case Report of Serratus Plane Catheter for Pain Management in a Patient With Multiple Rib Fractures and an Inferior Scapular Fracture. Issue 6 (15th March 2017) - Fu, Peter; Weyker, Paul D.; Webb, Christopher A. J.
Abstract : We placed a superficial serratus anterior plane catheter in an elderly woman with dementia and elevated clotting times who presented with multiple rib fractures after a mechanical fall. She was not a surgical candidate, and treatment consisted of conservative management with physical therapy and pain control. She was not a candidate for a patient-controlled analgesia regimen because of her dementia. Given her elevated international normalized ratio, thoracic epidural and paravertebral analgesia was also contraindicated. We placed an ultrasound-guided serratus anterior plane catheter, allowing titratable continuous infusion in a trauma patient, resulting in excellent analgesia without adverse effects.